2007
DOI: 10.1002/app.27550
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐containing terephthaldialdehyde adducts—Structure determination and their application as flame retardants in epoxy resins

Abstract: Two novel phosphorus-rich prepolymers based on epoxy novolac and terephthaldialdehyde and potential flame retardants, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 2,8-dimethyl-phenoxaphosphin-10-oxide (DPPO) were synthesised. The resultant flame-retardant epoxy resins were cured with 4,4 0 -diaminodiphenylmethane (DDM) and 4,4 0 -diamino-dicyclohexylmethane (PACM). Their flammability and burning behavior were characterised by UL 94 and LOI and compared with analogue prepolymers based on diethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The introduction of flame retardant molecules in the polymer backbone was also reported by Seibold et al who reacted phosphorus-rich molecules DOPO and DPPO with terphathaldialdehyde to form new bifunctional flame retardants for PWB (Figure 18) [78]. The novolac epoxy resins cured with DDM and the bifunctional phosphorus molecules reached UL 94-V0 rating with 1.02 and 1.45% phosphorus for the DOPO and DPPO derivatives respectively.…”
Section: Recent Development In Phosphorus Flame Retardantssupporting
confidence: 57%
“…The introduction of flame retardant molecules in the polymer backbone was also reported by Seibold et al who reacted phosphorus-rich molecules DOPO and DPPO with terphathaldialdehyde to form new bifunctional flame retardants for PWB (Figure 18) [78]. The novolac epoxy resins cured with DDM and the bifunctional phosphorus molecules reached UL 94-V0 rating with 1.02 and 1.45% phosphorus for the DOPO and DPPO derivatives respectively.…”
Section: Recent Development In Phosphorus Flame Retardantssupporting
confidence: 57%
“…PWB are low Tg, metal-resin adhesion, fabricating properties, dimensional stability, long-term reliability, and increased cost [5]. There are copious reports available based on DOPO and its derivatives [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], whereas little work has been presented on the basis of Fyrol PMP and aluminum diethylphosphinate-filled epoxies. Wu et al have studied the curing kinetics of epoxy cured with a stoichiometric amount of Fyrol PMP and showed that in the presence of a catalyst, the epoxy curing is completed at 150°C after 70 min [25].…”
mentioning
confidence: 99%
“…The title compound was synthesised by a modified literature method (Bronger et al, 2004). For other structurally related ligands, see: Levy et al (1965); Seibold et al (2008); Shau et al (2002).…”
Section: Related Literaturementioning
confidence: 99%